2020
DOI: 10.1088/2631-8695/ab7b38
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of rapid response self-powered photodetector using solution-processed triple cation lead-halide perovskite

Abstract: Self-powered photodetectors (PDs) are suitable for application in smart systems, image sensing and optical communications. Herein, a self-powered PD based on triple cation lead-halide perovskite (TCLP) is reported. We showed the effect of bromide concentration on the optical and structural properties of the TCLP films. Additionally, an environmental stability test was conducted and it was found that TCLP with 10% Br can remain stable for up to 128 days after exposure to ambient air. Using this material, a self… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 73 publications
0
6
2
Order By: Relevance
“…The responsivity and detectivity of self‐powered photodetectors obtained in the present study were compared with reported perovskite‐based sandwiched‐type devices, as shown in Figure . [ 8,19,42,45–52 ] The responsivity and detectivity reported in the present study are superior compared with prior relevant studies. The superior performance obtained from self‐powered photodetectors via CVD deposited perovskite films might be attributed to the high intrinsic quality of the perovskite films (high quality compact films and with no pinholes).…”
Section: Resultscontrasting
confidence: 62%
“…The responsivity and detectivity of self‐powered photodetectors obtained in the present study were compared with reported perovskite‐based sandwiched‐type devices, as shown in Figure . [ 8,19,42,45–52 ] The responsivity and detectivity reported in the present study are superior compared with prior relevant studies. The superior performance obtained from self‐powered photodetectors via CVD deposited perovskite films might be attributed to the high intrinsic quality of the perovskite films (high quality compact films and with no pinholes).…”
Section: Resultscontrasting
confidence: 62%
“…R and D* were calculated depend on that noise in the current noise is mainly dominated by shot noise. Compared with a previous study [21] appeared responsivity 0.99 A/W where the detectivity of 8.9 × 10 12 Jones, related to the improved morphology with a decrease in grain size and vacancies, which is reflected in the high performance level of our photodetector. By using on/off ratio as a measurement of photodetector repeatability, we obtained a high capacity that allows the photodetector to be operated repeatedly and with the same efficiency without any damage to the photodetector, as shown in figure 6…”
Section: Thin Films and Photodetector Fabricationcontrasting
confidence: 56%
“…The lower RMS value for the CsI­(PbBr 2 ) 0.99 (AgI) 0.01 perovskite film confirms the presence of additive AgI and that it can passivate the surficial morphology of the perovskite film. Also, the reduced surface roughness would produce fewer defects and traps in the interface between CsI­(PbBr 2 ) 0.99 (AgI) 0.01 and Spiro-OMeTAD layers, resulting in efficient charge extraction. …”
Section: Results and Discussionmentioning
confidence: 99%